Research on the energy transmission mode of a three-port DC–DC converter based on ultra-thin silicon steel - Hou, Lei; Zhao, Ming; Wang, Yixiao; Qu, Feng; Shao, Dan; Yang, Xin; Liu, Yang; Yang, Zhaoning (Frontiers in Electronics, 2024)
With the introduction of the China's "Carbon Peaking Action Plan Before 2030", the transformation of the power industry has released huge opportunities and potentials. The DC distribution network can well coordinate the contradiction between distributed power and grid access, fully develop the benefits of distributed energy, and become a new direction for the development of the power industry. However, the current traditional DC-DC converters have problems such as single topology structure and low power density, which can only complete one-way transmission of energy, which makes the distributed energy cannot be fully utilized. For the problem of distributed energy transfer, this thesis is based on a three-port DC-DC converter for low-voltage DC distribution network to realize energy transfer between DC distribution network, distributed energy and low-voltage load. Firstly, the energy transfer modes of the three-port DC-DC converter is introduced. Combined with the converter topology and energy transfer mode, a simplified equivalent model of the converter is established. The voltage gain characteristics and frequency characteristics of this converter are studied. Furthermore, the effects of the excitation inductance to primary resonance inductance ratio parameter k and quality factor Q on the voltage gain characteristics of the converter are discussed. On this basis, the resonant cavity design of the converter is based on the optimal selection of parameters k and Q so that the converter can meet the voltage gain requirements in both forward and reverse operation. The simulation results under different loads verify the reasonableness of the resonant cavity components selection.